Puppeteer Learning Model in the Perspective of the Cultural Inheritance System - Cahya (Pascasarjana ISBI Bandung Conference Series, 2025)
This article reveals the issue of the cultural inheritance system that applies to the Sundanese puppetry tradition in the form of the puppeteer learning model that applies in the Munggul Pawenang Putra Parakan Saat wayang studio, Bandung city. Cultural inheritance in this context is seen as a form of system for spreading the art of puppetry through non-formal education in art studios. In it there are stages of learning dalang which has become a traditional learning model in a dalang paguron. In principle, puppeteer students uphold the value and dignity of their puppetry which is realized through forms of puppeteering creativity as a form of aesthetic expression of their respective works. This research uses qualitative methods of analytical description. Operational research was not carried out fully directly in the field, but rather prioritized literature studies but also carried out interview methods with main and supporting sources. The output of this research is international journal articles, IPR and International Seminar. Keywords: Cultural heritage; model; stages of learning puppeteer